Entrepreneurship in Family vs. Non–Family Firms: A Resource–Based Analysis of the Effect of Organizational Culture - Zahra, Shaker A.; Hayton, James C.; Salvato, Carlo (Entrepreneurship Theory and Practice, 2004)
Organizational culture is an important strategic resource that family firms can use to gain a competitive advantage. Drawing upon the resource–based view (RBV) of the firm, this study examines the association between four dimensions of organizational culture in family vs. non–family businesses and entrepreneurship. Using data from 536 U.S. manufacturing companies, the results show a nonlinear association between the cultural dimension of individualism and entrepreneurship. Further, there are positive linear relationships between entrepreneurship and an external orientation, an organizational cultural orientation toward decentralization, and a long– versus short–term orientation. With the exception of an external orientation, each of these dimensions is significantly more influential upon entrepreneurship in family firms when compared with non–family firms.